2016
DOI: 10.4236/pp.2016.71008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicological Profile of a Polyherbal Formulation

Abstract: In current study toxicological profile of a commonly used herbal formulation was evaluated that is used extensively for gynecological disorders like menorrhagia, metrorrhagia, leucorrhea, irregular menstrual cycle, pre-menstrual syndrome and post-menopausal bleeding. It was also claimed to strengthen endometrium and ovaries. Since this herbal formulation was been used by a large number of population hence there was a need to assess acute and sub-chronic toxicity. Acute oral toxicity (LD50) was observed in albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The toxic effect of the PHF5 extract may be attributed to the presence of one or more phyto-compounds, which have a toxic impact on the animal model. Similar results were found in an acute and sub-acute toxicity study of a Pakistani polyherbal formulation [30,31] and in an investigation of Chinese traditional medicine when an herbal formula was used in patients. However, liver toxicity was attributed to overdosing [32].…”
Section: Resultssupporting
confidence: 82%
“…The toxic effect of the PHF5 extract may be attributed to the presence of one or more phyto-compounds, which have a toxic impact on the animal model. Similar results were found in an acute and sub-acute toxicity study of a Pakistani polyherbal formulation [30,31] and in an investigation of Chinese traditional medicine when an herbal formula was used in patients. However, liver toxicity was attributed to overdosing [32].…”
Section: Resultssupporting
confidence: 82%
“…A total of 40 Wistar strain albino rats of 200 ± 5 g (10 weeks of age), 30 mice of 30 ± 2 g (10 weeks of age), and 60 rabbits of 1000 -1500 g (10 months of age) were gathered from a retained and renowned animal house of Baqai Institute of Pharmaceutical Sciences (BIPS). Rabbits were selected for this evaluation because they have similar hematological variations to humans (29). All animals were housed in the animal house for 12/12-hour light/dark cycles at 25 ± 2°C temperature.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The liver photomicrographs showed that treatment of animals with the polyherbal mixtures did not induce any visible lesions or derangements in the examined organ. [77][78][79][80][81][82][83][84] However, in the sub-acute toxicity study of Hab-e-Kabad Noshadri tablets used for the treatment of hepatitis, enlargement of liver at doses of 100 and and 200 mg/kg/day, morphological changes with some damage in liver and kidney tissues of male and female animals was observed. Hence, prolonged use at higher dose i.e.…”
Section: Toxicological Activity Of Polyherbal Formulationsmentioning
confidence: 99%